So you want to be an inventor? - St. George, Judith, 1931-; Small, David, 1945- (New York : Puffin Books, 2005)
Presents some of the characteristics of inventors by describing the inventions of people such as Alexander Graham Bell, Thomas Edison, and Eli Whitney.
First published in the U.S. by Philomel Books, 2002.
Includes bibliographical references (p. 52).
Book Links (A.L.A.)
School Library Journal
Wilson's Children
5.1
Keywords: Inventions -- Juvenile literature; Inventors -- Juvenile literature; Inventions; Inventors; Inventions; Inventors